Pengembangan Bahan Ajar Berbasis Teori Van Hiele Menggunakan Flipbook pada Materi Bangun Datar untuk Siswa Kelas V Sekolah Dasar - Halil, Ibnu; Helsa, Yullys (Lembaga Yasin AlSys, 2025)
This research is motivated by the lack of use of teaching materials that utilize technology in the learning process. Learning resources that are less varied cause students to become bored, less active, and have difficulty understanding the material presented by the teacher during learning. Making teaching materials using technology that is quite difficult and complicated becomes an obstacle for teachers to create teaching materials that attract students' attention and interest in learning. So it is necessary to update teaching materials that are integrated with technological developments and student developments so that students are motivated and enthusiastic in the learning process. This study aims to develop teaching materials based on Van Hiele's theory using flipbooks on flat shape material for grade V elementary school students that are valid, practical and effective. This type of research is a Plomp model development research (R&D). The validity test shows valid teaching materials with a score of 67% (material), 91% (media), and 81% (language). Practicality test shows that the teaching materials are very practical with a score of 92% (students), and 95.55% (teachers) in the trial school, and 97.77% (teachers) and 99.82% (students) in the research school. Effectiveness test shows that the teaching materials are very effective to use in the trial school with a score of 94% (very effective) and in the research school with a score of 94.61% (very effective). Thus, the teaching materials are valid, practical, and effective to be used in mathematics learning for grade V of Elementary School.